Variations in high density cholesterol levels based on apolipoprotein E variant and exercise type - Chang, Huan-Cheng; Nfor, Oswald Ndi; Ho, Chien-Chang; Chen, Pei-Hsin; Liaw, Yung-Po (Frontiers in Genetics, 2023)
In various cross-sectional and longitudinal studies, exercise has been associated with cardiometabolic outcomes, including high-density lipoprotein (HDL) cholesterol. Exercise-induced changes in HDL cholesterol seem to be affected by genetic polymorphisms. In this study, we examined whether variant APOE rs7412 is involved in the association between HDL cholesterol and exercise. From adults assessed in Taiwan Biobank (TWB) between 2008 and 2019, we analyzed data from 57,638 normolipidemic subjects. To examine the association between exercise, APOE rs7412, and HDL cholesterol, a multiple linear regression model was used. A higher HDL was associated with both aerobic exercise (regression coefficient [mg/dL] beta- (β), 1.112; 95% confidence interval (CI); 0.903 to 1.322) and resistance exercise (β, 2.530; 95% CI, 2.093 to 2.966). In comparison with the APOE rs7412-CC genotype, the β was 2.589 (95% CI, 2.329 to 2.848) among those with the CT+TT genotype. Compared to adults who had the CC genotype and did not exercise (the CC/no exercise group), the β-coefficient determined for the different genotype and exercise groups was 1.135 (95% CI, 0.911 to 1.359) for the CC genotype and aerobic exercise group, 2.753 (95% CI, 2.283 to 3.322) for the CC genotype and resistance exercise group, 2.705(95% CI, 2.390 to 3.020) for the CT+TT genotype and no exercise group, 3.682 (95% CI, 3.218 to 4.146) for the CT+TT genotype and aerobic exercise group, and 3.855 (95% CI, 2.727 to 4.982) for the CT+TT genotype and resistance exercise group, respectively. This study demonstrates that self-reported aerobic and resistance exercise both raised HDL levels, yet resistance exercise was associated with a greater increase, particularly among Taiwanese subjects carrying the APOE rs7412-CT+TT genotype.